2012
DOI: 10.1371/journal.pone.0052617
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary History of Sarco(endo)plasmic Calcium ATPase (SERCA)

Abstract: Investigating the phylogenetic relationships within physiologically essential gene families across a broad range of taxa can reveal the key gene duplication events underlying their family expansion and is thus important to functional genomics studies. P-Type II ATPases represent a large family of ATP powered transporters that move ions across cellular membranes and includes Na+/K+ transporters, H+/K+ transporters, and plasma membrane Ca2+ pumps. Here, we examine the evolutionary history of one such transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Another potential set of candidate genes under selection that might be important for local adaptation are ATPase genes. ATPases move ions across cellular membranes, including Na + /K + , H + /K + and plasma membrane Ca 2+ pumps (Altshuler et al 2012), and play an important role in maintaining ion homeostasis under heat stroke or stress (Kourtis et al 2012). Similarly, a study of human populations indicated that heat adaptation is correlated with temperature, rainfall and latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential set of candidate genes under selection that might be important for local adaptation are ATPase genes. ATPases move ions across cellular membranes, including Na + /K + , H + /K + and plasma membrane Ca 2+ pumps (Altshuler et al 2012), and play an important role in maintaining ion homeostasis under heat stroke or stress (Kourtis et al 2012). Similarly, a study of human populations indicated that heat adaptation is correlated with temperature, rainfall and latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Several isoforms of SERCA pumps were present in mammals (e.g. three in Homo sapiens , Altshuler et al ) and land plants (e.g. four in A. thaliana ; Evans and Williams , Altshuler et al ).…”
Section: Methodsmentioning
confidence: 99%
“…three in Homo sapiens , Altshuler et al ) and land plants (e.g. four in A. thaliana ; Evans and Williams , Altshuler et al ). Adding to this list, we identified up to three isoforms in many genomes of the protozoal supergroups Stramenopiles, Alveolata and Rhizaria (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…The integrity of this gradient is actively maintained by the sarco-endoplasmic reticulum calcium ATPase (SERCA) pump, which transports two Ca 2ϩ ions into the ER at the expense of one ATP molecule (15). At least 14 different SERCA isoforms have been identified to date (16,17), and we have previously shown SERCA2b to be the most prevalent isoform expressed in the mouse pancreatic islet. We and others have also shown that ␤ cell SERCA2b levels are diminished in human and rodent models of T1D and T2D (18 -21), resulting in Ca 2ϩ dysregulation, impaired insulin secretion, and ER stress (19).…”
mentioning
confidence: 99%